A Novel Hybrid Fuzzy PD-TID Controller for Load Frequency Control of a Standalone Microgrid - Khokhar, Bhuvnesh; Dahiya, Surender; Parmar, K. P. Singh (Arabian journal for science and engineering (2011), 2021)
Uncertainties related to the power output from the renewable energy sources and low inertia of a standalone microgrid (SMG) demand a robust control strategy for continuous frequency control of the SMG. Consequently, this paper proposes a novel hybrid fuzzy proportional derivative–tilt integral derivative (FPD-TID) controller for the load frequency control (LFC) analysis of a SMG. Inspiration for the proposed controller comes from combining the advantages of both the FPD and the TID controllers. Gains of the proposed controller are optimized using a robust chaotic crow search algorithm (CCSA). In order to validate the proposed control scheme, comparative frequency deviation responses of the SMG are presented considering multiple disturbances. Also, the proposed controller is put to test for its sensitivity and robustness subject to a ± 30% variation in the SMG parameters and disconnection of various SMG subsystems, respectively. Since operational stability of the SMG is highly desirable under such circumstances, the proposed control scheme aims to achieve a trade-off between its performance and the operational stability of the SMG. The operational stability of the SMG is established through eigenvalue and root locus analysis.